CAUSE OF RELAPSE GASTRIC CANCER PATIENTS AFTER RADICAL TREATMENT - A. G. Baryshev; V. A. Porhanov; A. Y. Popov; A. N. Lishenko; N. V. Hachaturyan; D. A. Valyakis; M. V. Bodnya (Сибирский онкологический журнал)
Gastric cancer is one of the most common malignancies and the third most common cause of cancer-related death worldwide. Recent advances in the surgical treatment of gastric cancer are related to the use of extended lymph node dissection (D2), however, tumor characteristics such as tumor size, histological type, degree of differentiation as well as the presence of lymphovascular invasion and lymph node involvement are well known factors that influence long-term treatment outcomes. The purpose of the study was to analyze the survival rates in patients, who received curative treatment for locally advanced gastric cancer, depending on the extent of lymph node dissection, and tumor characteristics. Material and methods. Using the Kaplan-Meier method and analysis of variance, long-term treatment outcomes were analyzed in 662 patients with gastric cancer, who underwent either limited/standard lymph node dissection (D1) or extended lymph node dissection (D2). Results. The overall and 5-year survival rates were found to be significantly higher in patients undergoing a D2 lymph node dissection than in patients who had a D1 dissection, with the median survival time being 32.0 months compared to 46.0 months, respectively. Tumor characteristics, such as, disease stage, regional lymph node metastasis and invasion grade (poorly differentiated tumor) had a greater impact on survival than the extended lymph node dissection. Conclusion. Extended lymph node dissection (D2) should be performed routinely in the curative surgical treatment of gastric carcinoma. The beneficial effect from D2 lymph node dissection was observed in gastric cancer patients with different histological characteristics such as the type, grade and depth of tumor invasion. The standardization of surgical procedures and detection of the tumor at an early stage lowered the operative risk in the treatment of gastric cancer.